Pergeseran Nilai Tradisi Perahu Baganduang di Desa Banjar Padang Kecamatan Kuantan Mudik Kabupaten Kuantan Singingi - Rumzi, Aska Elfita; Indrawati, Indrawati (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to determine the shift in the function of the Baganduang Boat tradition in Banjar Padang Village, Kuantan Mudik District, Kuantan Singingi Regency. The theory used to analyze the research is Koentjaraningrat's theory of local wisdom values. Data analysis in this research used a descriptive method with a qualitative approach, with a total of 6 research informants. Data collection was carried out using interview and documentation techniques, analysis techniques using data reduction, data presentation and data verification. The results of this research indicate that currently the Baganduang Boat tradition has experienced several shifts in function. The factors that cause a shift in the function of the Baganduang Boat tradition in Kuantan Mudik District are due to globalization factors, modernization factors, tourism factors, and social change factors.